Determinan Faktor Prediabetes di Kota Jambi Tahun 2019 - Sovia Sovia; Netha Damayantie; Nur Insani (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Prediabetes is a threshold condition of diabetes. This situation is often unknown or understood by the public so the incidence rate is undocumented. This research aims to identify the incidence of Prediabetes and its risk factors. The design of the study was cross sectional with a population of 260 and a sample count of 169 people taken purposive sampling. This research was conducted at one of the health education institutions in Jambi City in October and November 2019. Data collection using questionnaires and fasting blood sugar levels. Data analysis uses frequency proportions, Chi-Square, and logistic regression. The results showed a prediabetes incidence of 21.9% and factors affecting it were age (p=0.038, OR 0.423, 95% CI 0.185-0.966), exercise (p=0.002, OR 0.228, 95% CI 0.083-0.626), smoking behavior (p=0.003, OR 3,106, 95% CI 1,425-6,770), and nutritional status (p=0.028). Based on the results of research recommended to promote the activities of Healthy Community Movement in Jambi City and the need to hold posbindu activities regularly every month.